The Big Questions of "ICT4D" - Toyama, Kentaro; Peters, Teresa (Microsoft, 2009)
There is no clear consensus on the appropriate role for information and communications technology in social and economic development to improve the lives of the poor around the world. The field is fraught with conflicting views about what is most important, what works best, how to measure benefits, what processes lead to good solutions, and who should pay for it all. And, because ICT4D is still young and assessment is difficult, concrete evidence of positive outcomes are scant. Thus, instead of adding to the loud, but weakly supported rhetoric in ICT4D, this paper presents 13 “hot button” questions that characterize the debate in the field today, and it attempts to summarize the arguments on all sides. The hope is that this will help the reader navigate through the various issues in ICT4D and identify the questions most worthy of further consideration.